The Clinical Effects of Carthami-Flos Pharmacopuncture on Posterior Neck pain of Menopausal Women - Jae-Yeon Park; Kyung-Jin Yun; You-Jin Choi; Min-Seok Kim; Sung-Jin Yu; Cham-Kyul Lee; Jeong-Du Roh; Eun-Yong Lee (Korean Pharmacopuncture Institute, 2011)
Objectives: The purpose of this research was to examine the effect of Carthami-Flos Pharmacopuncture on posterior neck pain of menopausal women. Methods: We treated 20 female patients with neck pain patient(45-60 yr) into two groups and treated Group A with Carthami-Flos Pharmacopuncture and common acupuncture and Group B with common acupuncture. The efficacy of treatment was measured by VAS, NDI and MENQOL scores of before and after 30 days to start treatment. Results: Both group A and B represented effective improvement in VAS and NDI of neck pain and MENQOL scores. And group A was more effective than B group statistically. Conclusions: It was suggested that Carthami-Flos Pharmacopuncture treatment might have effect on posterior neck pain treatment of menopausal women.